1978
DOI: 10.1099/0022-1317-41-3-563
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Transduction Process by SPP1 Phage

Abstract: SUMMARYThe conditions for optimal transduction efficiency of the Bacillus subtilis phage SPPI have been investigated. By irradiating transducing lysates with u.v. light we have been able to obtain a fivefold increase in the number of transductants and to reduce strongly the interference caused by infective particles. Any dependence of SPPI transduction on PBSX induction has been ruled out by the use of xin mutants, which are unable to induce the defective phage. SPPI mediated transduction is susceptible to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Not only phage DNA but also B. subtilis chromosomal and plasmid DNAs can be packaged into SPP1 particles, although with very low efficiency. Therefore, the virulent SPP1 is also a transducing phage (4,7,33). The molecular weight of transducing DNA contained in SPP1 particles is identical to that of infective phage DNA.…”
mentioning
confidence: 99%
“…Not only phage DNA but also B. subtilis chromosomal and plasmid DNAs can be packaged into SPP1 particles, although with very low efficiency. Therefore, the virulent SPP1 is also a transducing phage (4,7,33). The molecular weight of transducing DNA contained in SPP1 particles is identical to that of infective phage DNA.…”
mentioning
confidence: 99%
“…Phage PBSl was used as described by Moir et al (1979). Phage SPPl was used as described by Ferrari et al (1978) except that vegetative cells were used, rather than spores, to prepare lysates.…”
mentioning
confidence: 99%
“…Generalized transduction by SPP 1 has been repeatedly demonstrated (Ferrari et al, 1978;Lencastre & Archer, 1980;Yasbin & Young, 1974). We have found that lysates of 41c, 22a, p15 and SF6 share this capacity.…”
mentioning
confidence: 99%